2020
DOI: 10.1371/journal.pone.0234705
|View full text |Cite
|
Sign up to set email alerts
|

Patient-physician discrepancy in the perception of immune-mediated inflammatory diseases: rheumatoid arthritis, psoriatic arthritis and psoriasis. A qualitative systematic review of the literature

Abstract: Introduction Recommendations on chronic diseases management emphasise the need to consider patient perspectives and shared decision-making. Discrepancies between patients and physicians' perspectives on treatment objectives, disease activity, preferences and treatment have been described for immune-mediate inflammatory diseases. These differences could result on patient dissatisfaction and negatively affect outcomes. Objective To describe the degree of patient-physician discrepancy in three chronic immune-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…11 Patient and physician perspectives are known to differ when reporting on disease severity. 27 In line with published data from other longitudinal studies with outpatients, symptoms progression was also heterogeneous. 1,[8][9][10][11] Some symptoms such as "Feverish", "Vomiting", "Confusion", and "Rash" resolved within the first week from randomisation.…”
Section: Discussionsupporting
confidence: 84%
“…11 Patient and physician perspectives are known to differ when reporting on disease severity. 27 In line with published data from other longitudinal studies with outpatients, symptoms progression was also heterogeneous. 1,[8][9][10][11] Some symptoms such as "Feverish", "Vomiting", "Confusion", and "Rash" resolved within the first week from randomisation.…”
Section: Discussionsupporting
confidence: 84%
“…5 The discordance between patient and physician assessment of disease has been previously reported in a number of immunemediated inflammatory diseases including PsA. 9 In the study by Beckers et al, 5 some of the discordance is likely to be due to the different components of the PASDAS, DAPSA, and ASDAS instruments. Each of these instruments has slightly different representations of patient and physician components and it is worth considering that impact should be assessed along side activity, such that symptoms from noninflammatory causes can be addressed accordingly.…”
Section: See Peripheral Spa Measures Page XXXmentioning
confidence: 92%
“…Moreover, Fusama et al [ 6 ] demonstrated that biologic treatment, which enables clinical, structural and functional remission, improved patients’ QOL. However, Taylor et al [ 7 ] reported that patients’ psychological and social needs were not being met with their current health status because of the large patient–physician discrepancy regarding RA management [ 8 ].…”
Section: Introductionmentioning
confidence: 99%